Conducting the Needs Assessment #8: The Borich Model - Olivia Caillouet; Amy Harder (EDIS, 2022)
This eighth publication in the Conducting the Needs Assessment series provides Extension professionals and other service providers with directions for how to use the Borich model to collect data about the training needs of a target audience and how to use that data to improve programming. Written by Olivia Caillouet and Amy Harder; published by the UF/IFAS Department of Agricultural Education and Communication; 5 pp. https://edis.ifas.ufl.edu/wc415